I am unable to understand how the negation of a sentence into CNF actually makes sense, hopefully somebody can explain it to me in understandable terms!
Given the sentence: If the battery is charged (A) and the screen is not cracked (B) then the phone is working (C)
The following makes perfect sense:
(A ∧ B) => C
I cannot get my head around how the negated form is true or how it works:
¬A ∨ ¬B ∨ C
I am struggling because "not A" means if the battery is not charged? So I cannot see how if the battery is not charged or the "screen is cracked" or the "phone is usable".
If A is false, so battery is not charged, how is that applying ¬A to it does not make it now true?
Any help would be appreciated.